A Place in the World: Vulnerability, Well-Being, and the Ubiquitous Evaluation That Animates Participation in Institutional Processes - Creed, W. E. Douglas; Hudson, Bryant A.; Okhuysen, Gerardo A.; Smith-Crowe, Kristin (Academy of Management Review, 2022)
We explain how and why people become motivated to participate in institutional processes. Responding to recent efforts to address the micro and meso in institutional analysis, we introduce two interrelated constructs, a person’s embodied world of concern and a community’s shared world of concern, which shape how people experience, evaluate, and participate in institutional arrangements. The world of concern, which is the product of people’s sedimented experiences of thriving and suffering, becomes the basis for their commitments to antagonisms towards certain social arrangements. The world of concern, as a lens, sheds light on the complex ways the macro, meso, and micro levels are co-implicated in constructing commitments and attachments that animate action in institutional arenas by providing a new metaphor, one that links the realism of participant concerns to the micro dynamics that underpin institutions. We conclude with a discussion of the implications of these ideas for future research.